High-Frequency Deep Brain Stimulation of the Substantia Nigra Pars Reticulata Facilitates Extinction and Prevents Reinstatement of Methamphetamine-Induced Conditioned Place Preference - Zhang, Libo; Meng, Shiqiu; Chen, Wenjun; Chen, Yun; Huang, Enze; Zhang, Guipeng; Liang, Yisen; Ding, Zengbo; Xue, Yanxue; Chen, Yun; Shi, Jie; Shi, Yu (Frontiers in Pharmacology, 2021)
Persistent and stable drug memories lead to a high rate to relapse among addicts. A number of studies have found that intervention of addiction-related memories can effectively prevent relapse. Deep brain stimulation (DBS) exhibits distinct therapeutic effects and advantages in the treatment of neurological and psychiatric disorders. In addition, recent studies have also found that substantia nigra pars reticulata (SNr) could serve as a promising target in the treatment of addiction. Therefore, the present study aimed to investigate the effect of DBS of SNr on the reinstatement of drug seeking behaviors. Electrodes were bilaterally implanted into the SNr of rats before training of methamphetamine-induced conditioned place preference (CPP). High frequency (HF) or low frequency (LF) DBS was then applied to SNr during the drug-free extinction sessions. We found that HF DBS during the extinction sessions facilitated extinction of methamphetamine-induced CPP and prevented drug-primed reinstatement, while LF DBS impaired the extinction. Both HF and LF DBS did not affect locomotor activity or induce anxiety-like behaviors of rats. Finally, HF DBS had no effect on the formation of methamphetamine-induced CPP. In conclusion, our results suggest that HF DBS of SNr could promote extinction and prevent reinstatement of methamphetamine-induced CPP, and SNr may serve as a potential therapeutic target in the treatment of drug addiction.